Repurchase Intention in Eco-Labeled Products: The Roles of Green Marketing and Perceived Value - Kyrbi, Ramanda; Suryadi, Nanang (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This study aims to examine the effect of green marketing and perceived value on the repurchase intention of AQUA consumers. Classified as explanatory research, it seeks to elucidate the causal relationships between variables through hypothesis testing using a quantitative approach. The variables studied include green marketing (X1), perceived value (X2), and repurchase intention (Y). Using a non-probability sampling method, which is the purposive sampling technique, 130 people with the minimum age of 17 years who live in Malang City and have purchased AQUA products were selected as the respondents. The research instrument underwent validity and reliability tests, while data quality was assessed using the classical assumption test, and the data analysis was conducted through multiple linear regression. All statistical processes, including the hypothesis testing, were performed using the Statistical Package for the Social Sciences (SPSS) version 30.0. The results suggest that green marketing has a positive but statistically insignificant effect on repurchase intention, whereas perceived value has a significant positive effect on repurchase intention